COVID‐19 and the Mental Capacity Act in care homes: Perspectives from capacity professionals. (9th February 2022) - Kuylen, Margot; Wyllie, Aaron; Bhatt, Vivek; Fitton, Emily; Michalowski, Sabine; Martin, Wayne
Abstract: This study explores the experiences of professionals who worked with care home residents with impaired mental capacity in England and Wales during the COVID‐19 pandemic. It explores (i) how competing risks were balanced and (ii) how the Mental Capacity Act (MCA) functioned in care homes under pandemic conditions, with particular focus on its associated Deprivations of Liberty Safeguards (DoLS) and Independent Mental Capacity Advocacy (IMCA) systems. Between March and May 2021, we held an online survey and five focus groups aimed at professionals who worked in or with care homes during the pandemic. The study explored issues pertaining to residents with impaired mental capacity, alongside several other topics on which we report elsewhere. For this paper, we filtered data to only include responses from 'capacity professionals'. The resulting sample comprised 120 (out of 266) survey participants and 18 (out of 22) focus group participants. We performed manifest content analysis on the filtered data and found that (1) participants reported a 'massive discrepancy' between the ways different care homes balanced the risk of COVID‐19 infection with the risks associated with severe restrictions. (2) Some suggested this was due to vague guidance, as well as care home type and size. Participants told us the pandemic (3) obstructed smooth operation of statutory safeguards designed to protect residents' human rights and (4) resulted in confusion about the remit of the MCA during a public health crisis. Our findings raise concerns about the impact of pandemic‐related measures upon care home residents with impaired mental capacity. We urge further exploration and analysis of (a) the variability and inconsistency of restrictions applied at care homes, (b) the strain placed on key safeguards associated with the MCA, (c) uncertainty about the remit of the MCA during a public health crisis and (d) the human rights implications hereof.